Answer:
(- 4, - 12 ) , (4, 12 )
Step-by-step explanation:
Given the 2 equations
y = 3x → (1)
y = x² + 3x - 16 → (2)
Substitute y = x² + 3x - 16 into (1)
x² + 3x - 16 = 3x ( subtract 3x from both sides )
x² - 16 = 0 ( add 16 to both sides )
x² = 16 ( take the square root of both sides )
x = ±
= ± 4
Substitute these values into (1) for corresponding values of y
x = - 4 : y = 3 × - 4 = - 12 ⇒ (- 4, - 12 )
x = 4 : y = 3 × 4 = 12 ⇒ (4, 12 )
5*23
Note 23 = 20 + 3
5*23 = 5*(20 + 3) and by distributive property
5*23 = 5*20 + 5*3 = 100 + 15 = 115
= 115
Answer:
An apple costs $2.25. A mango costs $1.25.
Step-by-step explanation:
Let a = price of 1 apple.
Let m = price of 1 mango.
Cameron:
4 apples + 7 mangoes ----> total $17.75
4a + 7m = 17.75
Gavin:
2 apples + 5 mangoes ----> total $10.75
2a + 5m = 10.75
We have a system of 2 equations in 2 unknowns.
4a + 7m = 17.75
2a + 5m = 10.75
We can use the elimination method to eliminate the variable <em>a</em>. Rewrite the first equation. Multiply both sides of the second equation by -2 and write below it. Then add the equations.
4a + 7m = 17.75
(+) -4a - 10m = -21.5
---------------------------------
-3m = -3.75
Divide both sides by -3.
m = 1.25
<em>A mango costs $1.25.</em>
Now we use the first equation and substitute 1.25 for <em>m</em> and solve for <em>a</em>.
4a + 7m = 17.75
4a + 7(1.25) = 17.75
4a + 8.75 = 17.75
4a = 9
a = 2.25
<em>An apple costs $2.25.</em>
Answer: An apple costs $2.25. A mango costs $1.25.